2011
DOI: 10.1007/s12052-011-0323-8
|View full text |Cite
|
Sign up to set email alerts
|

The Inability of Primary School to Introduce Children to the Theory of Biological Evolution

Abstract: A great number of research papers in the English literature of science education present difficulties pupils have in understanding natural selection. Studies show that children have essentialist and teleological intuitive ideas when dealing with organisms and that these biases hinder their ability to understand the theory of evolution by natural selection. Consequently, it is interesting to ascertain if and how the school education offered today deals with the problem, i.e., helps the children confront these b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 33 publications
2
35
0
3
Order By: Relevance
“…Despite its fundamental importance in biology and many other research fields, studies have shown that biological evolution is not yet accepted as a valid scientific theory by an important fraction of citizens from different nations (Miller et al 2006), and that misconceptions about evolution are frequent and shared by the general public, students, and teachers from several countries (Rutledge and Warden 2000;Nehm and Reilly 2007;Prinou et al 2011;Spiegel et al 2012). Furthermore, these misconceptions revealed to be persistent and difficult to overcome, even when applying learning programs specifically designed to promote such conceptual changes (Bishop and Anderson 1986;Nehm and Reilly 2007).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite its fundamental importance in biology and many other research fields, studies have shown that biological evolution is not yet accepted as a valid scientific theory by an important fraction of citizens from different nations (Miller et al 2006), and that misconceptions about evolution are frequent and shared by the general public, students, and teachers from several countries (Rutledge and Warden 2000;Nehm and Reilly 2007;Prinou et al 2011;Spiegel et al 2012). Furthermore, these misconceptions revealed to be persistent and difficult to overcome, even when applying learning programs specifically designed to promote such conceptual changes (Bishop and Anderson 1986;Nehm and Reilly 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These observations led several researchers to propose an early exploration of evolutionary biology at elementary school or even kindergarten (Nadelson et al 2009;Hermann 2011;Wagler 2010, 2012 andreferences therein). In agreement with this view, several countries explicitly include, or intend to include, evolution in their official curricula for elementary schools (see as examples the Canadian curriculum or the United Kingdom draft curriculum in Additional file 1; Berti et al, 2010 andPrinou et al 2011 for Italian and Greek curricula, respectively). However, in some of these cases evolutionary mechanisms are not explored and evolution is only mentioned in the context of adaptation, preventing students to understand the real impact of evolution in biological diversity (Prinou et al 2011;Wagler 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[26][27][28] It appears that possession of PCK, on its own, may not be adequate for educators to present the biological adaptation content in a manner accessible to students. In response, this lesson exploits the use of a four-legged mobile robot and situated cognition 10 techniques to produce a storyline embedded with important concepts of biological adaptation.…”
Section: Biological Adaptationmentioning
confidence: 99%